The depth, duration, and degree of outpatient pediatric polypharmacy in Colorado fee‐for‐service Medicaid patients†. (7th August 2015) - Feinstein, James A.; Feudtner, Chris; Valuck, Robert J.; Kempe, Allison
Abstract Background and Objectives Outpatient pediatric polypharmacy is poorly characterized. Identification of at‐risk populations has clinical implications for pharmacy case management programs. We described the degree of exposure to polypharmacy using parameters of depth (concurrent medication count) and duration, reported commonly dispensed medications and exposure to three example potential drug–drug interactions by different depths of polypharmacy, and determined patient characteristics associated with exposure to increased degrees (a function of depth and duration) of polypharmacy. Methods Retrospective cohort study of Colorado fee‐for‐service Medicaid patients aged <18 years with 12 months of continuous enrollment. We calculated depth of polypharmacy using daily concurrent medication counts and duration of polypharmacy using days exposed to a certain depth. Multinomial logistic regression was used to assess patient characteristics associated with different degrees of polypharmacy. Results Of 242 230 patients, 35% percent were exposed to any depth of polypharmacy, most commonly to anti‐infective medications. Patients with higher depth polypharmacy were exposed to less common medications (psychotropic drugs, anticonvulsants, cardiovascular agents, and opioids) and to higher rates of exposure to potential drug–drug interactions. Of 47 972 patients exposed to ≥3 concurrent medications, 50% were exposed for <15 days, 25% for 15–38 days, 15% for 39–111 days, and 10% for 112–327 days. High‐degree polypharmacy was associated with increasing age, male gender, and presence of a complex chronic condition. Conclusions Outpatient pediatric polypharmacy occurs to a substantial degree for a small but vulnerable population of children, who may be candidates for pharmacy case management. We must determine whether increased exposure to high‐degree polypharmacy causes harm. Copyright © 2015 John Wiley & Sons, Ltd.